Replication Data for "Malnutrition and Climate Patterns in the Arid and Semi-arid Lowlands of Kenya: A Resilience Analysis Based on a Pseudo-panel Dataset" - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Resilience of food security in the arid and semi-arid lowlands (ASAL) in Kenya, were assessed using repeated cross-sectional data (collected in 1993, 1998, 2003, and 2008). We measure short- and long-term food security in response to changing agro-climatic conditions, using indicators of child and woman nutritional status. Since measurements over time on the same units of analysis are not available, synthetic cohorts of individuals (children and women) having similar characteristics have been reconstructed, resulted in a pseudo-panel dataset. The dataset is used to observe resilience to agro-climatic shocks, including temperature increases, drought, and changes in vegetation cover.